The ionospheric responses to the 11 August 1999 solar eclipse: observations and modeling - H. Le (Annales Geophysicae, 2008)
A total eclipse occurred on 11 August 1999 with its path of totality passing over central Europe in the latitude range 40°–50° N. The ionospheric responses to this eclipse were measured by a wide ionosonde network. On the basis of the measurements of foE, foF1, and foF2 at sixteen ionosonde stations in Europe, we statistically analyze the variations of these parameters with a function of eclipse magnitude. To model the eclipse effects more accurately, a revised eclipse factor, FR, is constructed to describe the variations of solar radiation during the solar eclipse. Then we simulate the effect of this eclipse on the ionosphere with a mid- and low-latitude ionosphere theoretical model by using the revised eclipse factor during this eclipse. Simulations are highly consistent with the observations for the response in the E-region and F1-region. Both of them show that the maximum response of the mid-latitude ionosphere to the eclipse is found in the F1-region. Except the obvious ionospheric response at low altitudes below 500 km, calculations show that there is also a small response at high altitudes up to about 2000 km. In addition, calculations show that when the eclipse takes place in the Northern Hemisphere, a small ionospheric disturbance also appeared in the conjugate hemisphere.